Impacts of the COVID-19 Pandemic on Children's Sugary Drink Consumption: A Qualitative Study - Sylvetsky, Allison C.; Kaidbey, Jasmine H.; Ferguson, Kacey; Visek, Amanda J.; Sacheck, Jennifer (Frontiers in Nutrition, 2022)
The coronavirus (COVID-19) pandemic has caused striking alterations to daily life, with important impacts on children’s health. Spending more time at home and out of school due to COVID-19 related closures may exacerbate obesogenic behaviors among children, including consumption of sugary drinks (SDs). This qualitative study aimed to investigate effects of the pandemic on children’s SD consumption and related dietary behaviors. Children 8-14 years old and their parent (n=19 dyads) participated in an in-depth qualitative interview. Interviews were recorded, transcribed verbatim, and independently coded by two coders, after which, emergent themes and subthemes were identified, and representative quotations selected. Although increases in children’s SD and snack intake were almost unanimously reported by both children and their parents, increased frequency of cooking at home and preparation of healthier meals were also described. Key reasons for children’s higher SD and snack intake were having unlimited access to SDs and snacks and boredom while at home. Parents also explained that the pandemic impacted their oversight of the child’s SD intake, as many parents described loosening prior restrictions on their child’s SD intake and/or allowing their child more autonomy to make their own dietary choices during the pandemic. These results call attention to concerning increases in children’s SD and snack intake during the COVID-19 pandemic. Intervention strategies to improve the home food environment, including reducing the availability of SDs and energy-dense snacks and providing education on food parenting are needed.